New radiocarbon dating and demographic insights into San Juan ante Portam Latinam, a possible Late Neolithic war grave in North‐Central Iberia. Issue 3 (15th March 2018) - Fernández‐Crespo, Teresa; Schulting, Rick J.; Ordoño, Javier; Duering, Andreas; Etxeberria, Francisco; Herrasti, Lourdes; Armendariz, Ángel; Vegas, José I.; Bronk Ramsey, Christopher
Abstract: Objectives: San Juan ante Portam Latinam is one of a small number of European Neolithic sites meeting many of the archaeological criteria expected for a mass grave, and furthermore presents evidence for violent conflict. This study aims to differentiate between what is potentially a single episode of deposition, versus deposition over some centuries, or, alternatively, that resulting from a combination of catastrophic and attritional mortality. The criteria developed are intended to have wider applicability to other such proposed events. Material and Methods: Ten new AMS 14 C determinations on human bone from the site, together with previously available dates, are analyzed through Bayesian modeling to refine the site's chronology. This is used together with the population's demographic profile as the basis for agent‐based demographic modeling. Results: The new radiocarbon results, while improving the site's chronology, fail to resolve the question whether the burial represents a single event, or deposition over decades or centuries—primarily because the dates fall within the late fourth millennium BC plateau in the calibration curve. The demographic modeling indicates that the population's age and sex distribution fits neither a single catastrophic event nor a fully attritional mortality profile, but instead may partake of elements of both. Discussion: It is proposed that San Juan ante Portam Latinam was used as burial place for the mainly adolescent and adult male dead of a particular or multiple violent engagements (e.g., battles), while previously or subsequently seeing use for attritional burial by other members of one or more surrounding communities dead over the course of a few generations. The overall bias towards males, particularly to the extent that many may represent conflict mortality, has implications for the structure of the surviving community, the members of which may have experienced increased vulnerability in the face of neighboring aggressors.